Role of emotional factors in learning Ukrainian as a foreign language at higher school - Ivanna, Struk; Ivanna (International Journal of Higher Education, 2020)
The emotional component of the educational process has been stated to be an essential factor of the formation of interest of a foreign student to learn the Ukrainian language as a foreign one. As it is one of the effective ways to improve of effective studying, rationalization and optimization of teaching methodology, based on analysis of the row of theoretical, methodological and experimental investigations in branches of psychology, psycho-linguistics, intercultural communication and pedagogy of the higher school. It has been indicated, that the principle of emotionality belongs to some basic principles of personal-oriented approach to studying. The theoretical and methodological analysis of directions of emotions implementation has been conducted in the process of didactics and communication, productive ways and methods of actualization of emotional factor have been developed at classes of Ukrainian as a foreign language; cultural peculiarities of apprehension of the emotional component of the educational process by different ethnic groups have been investigated. It has been proved, that satisfaction or dissatisfaction of communicative need of an international student generates positive or negative emotions, which influence on communicative activity, educational process, and consequently, on the process of cognition as a whole. The empirical part of the investigation was conducted based on interrogation of foreign students of Higher State Educational Institution of Ukraine. It aimed to detect national features of emotions perception by representatives of different nationalities (students from India, Africa and Arabic countries). The analysis showed that such factors as students do not see their progress in learning a language, difficulties in language understanding on hearing, the great synonymous potential of Ukrainian language become reasons for negative emotions in the process of learning Ukrainian as a foreign language, i.e. disappointment, indifference, concern, fear, dispossession. The group of effective methods has been distinguished for the provision of learning emotionality: verbal, extra-linguistic and activity-role. It has been found out, that emotional stimulation belongs to effective methods of activation of communicative as well as educational activity as a whole. Methodological recommendations are distinguished, which are specific for teaching foreign students concerning the realization of the principle of emotionality in multicultural different ethnic students’ audience.
Role of emotional factors in learning Ukrainian as a foreign language at higher school
Keywords: emotions, methods of emotionality, communicative act, personality-oriented approach, motivation, Ukrainian language as a foreign one, intercultural communication, a foreign student